Cordelia's honor - Bujold, Lois McMaster; Bujold, Lois McMaster (Riverdale, NY : Baen ; New York : Distributed by Simon & Schuster, 1996)
Made an outcast after being forced into an unwanted marriage with her arch enemy, Cordelia Naismith finds further trouble when her husband is made the guardian of the infant heir to the imperial throne. Original.
Shards of honor -- Barrayar.
"A Baen Books original"--T.p. verso.
80983
Keywords: Science fiction, American